2017
DOI: 10.1111/ffe.12586
|View full text |Cite
|
Sign up to set email alerts
|

Effect of intermetallic particles and grain boundaries on short fatigue crack growth behaviour in a cast Al–4Cu–3Ni–0.7Si piston alloy

Abstract: The short fatigue crack growth behaviour in a model cast aluminium piston alloy has been investigated. This has been achieved using a combination of fatigue crack replication methods at various intervals during fatigue testing and post‐mortem analysis of crack profiles. Crack–microstructure interactions have been clearly delineated using a combination of optical microscopy, scanning electron microscopy and electron backscatter diffraction. Results show that intermetallic particles play a significant role in de… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
7
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 12 publications
(7 citation statements)
references
References 67 publications
0
7
0
Order By: Relevance
“…Figure a shows that the unHIPped Al0.7Si alloy microstructure mainly comprises the α ‐Al matrix and a network of intermetallic compounds. The secondary dendrite arm spacing (SDAS) was measured using the line intercept method and found to be ≈37.3 ± 10 μm and the volume fraction ( V f ) of the intermetallics was measured and found to be ≈12.1 ± 2.2% . Figure a also shows an intermetallic cluster in the unHIPped microstructure.…”
Section: Results and Analysismentioning
confidence: 98%
“…Figure a shows that the unHIPped Al0.7Si alloy microstructure mainly comprises the α ‐Al matrix and a network of intermetallic compounds. The secondary dendrite arm spacing (SDAS) was measured using the line intercept method and found to be ≈37.3 ± 10 μm and the volume fraction ( V f ) of the intermetallics was measured and found to be ≈12.1 ± 2.2% . Figure a also shows an intermetallic cluster in the unHIPped microstructure.…”
Section: Results and Analysismentioning
confidence: 98%
“…Research in this field has identified that at low loading most of the component life is used for the crack initiation phase [3], while at high loading the component life is used for the crack propagation phase [4,5]. Crack initiation and growth in the early stages are strongly influenced by the microstructure of the material [6][7][8]. To determine the effect of microstructure on the damage process, a study was carried out on an early stage damage due to fatigue loading.…”
Section: Introductionmentioning
confidence: 99%
“…Pores were usually considered more detrimental to fatigue properties than oxide film. Several technologies such as hot isostatic pressing (HIP) can reduce pores of Al‐Si alloys with simple geometries . However, their application on piston alloys with complex structure involving thin‐wall sections was seldom reported.…”
Section: Introductionmentioning
confidence: 99%
“…Several technologies such as hot isostatic pressing (HIP) can reduce pores of Al-Si alloys with simple geometries. [30][31][32][33] However, their application on piston alloys with complex structure involving thin-wall sections was seldom reported. The pistons without casting defects may be hardly achieved.…”
Section: Introductionmentioning
confidence: 99%